2005
DOI: 10.1002/ejic.200500308
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of the [η2‐Bis(tert‐butylsulfonyl)acetylene](carbonyl)(η5‐cyclopentadienyl)cobalt Complex Towards Electron‐Rich and ‐Poor Acetylenes

Abstract: Keywords: Alkynes / Cobalt / Cyclopentadienyl ligands / N ligandsThe electron-rich aminoacetylenes Et 2 NC 2 R (2a-c, R = SPh, PPh 2 , and Ph, respectively) react smoothly with [η 2 -bis(tertbutylsulfonyl)acetylene](carbonyl)(η 5 -cyclopentadienyl)cobalt (1) to form the donor-acceptor stabilized (η 4 -cyclobutadiene)cobalt complexes 3a-c in good yields. However, treatment of the electron-poor borylacetylenes 2d-f with the cobalt complex 1 does not lead to the expected (η 4 -cyclobutadiene)cobalt complexes. Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Reaction of (A) with butadiynes, bis(methylseleno)butadiyne and (methylthio)(trimethylsilyl)butadiyne resulted in the compounds 309 and 310, respectively, whereas reaction with bis(methylthio)hexatriyne resulted in a dinuclear CpCo-stabilized cyclobutadiene complex 311 bridged by one acetylene moiety as a mixture of two stereoisomers [111]. Sulfur bridged complex 312 was obtained as a single product from the reaction of two equivalents of (A) with (PhC 2 ) 2 S in moderate yield [113].…”
Section: Cobalt Sandwich Compounds Of the Type (η 5 -Cp)co(η 4 -C 4 Rmentioning
confidence: 98%
See 2 more Smart Citations
“…Reaction of (A) with butadiynes, bis(methylseleno)butadiyne and (methylthio)(trimethylsilyl)butadiyne resulted in the compounds 309 and 310, respectively, whereas reaction with bis(methylthio)hexatriyne resulted in a dinuclear CpCo-stabilized cyclobutadiene complex 311 bridged by one acetylene moiety as a mixture of two stereoisomers [111]. Sulfur bridged complex 312 was obtained as a single product from the reaction of two equivalents of (A) with (PhC 2 ) 2 S in moderate yield [113].…”
Section: Cobalt Sandwich Compounds Of the Type (η 5 -Cp)co(η 4 -C 4 Rmentioning
confidence: 98%
“…Compounds 303 -308 have been synthesized by reaction of (A) with bis(methylseleno)acetylene [111], bis(methyltelluro)acetylene [111], bis(t-butoxy)acetylene [112], 2-(diethylamino)-1-phenylthioacetylene [113], 2-(diethylamino)-1-(diphenylphosphanyl)acetylene [113] and 2-(diethylamino)-1-phenylacetylene [113], respectively. Reaction of (A) with butadiynes, bis(methylseleno)butadiyne and (methylthio)(trimethylsilyl)butadiyne resulted in the compounds 309 and 310, respectively, whereas reaction with bis(methylthio)hexatriyne resulted in a dinuclear CpCo-stabilized cyclobutadiene complex 311 bridged by one acetylene moiety as a mixture of two stereoisomers [111].…”
Section: Cobalt Sandwich Compounds Of the Type (η 5 -Cp)co(η 4 -C 4 Rmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that diagonal tert-butyl groups are di- Table 2. Comparison of the relevant bond lengths and angles (with standard deviation) of 11, 13 [17] and 14. [18] All distances are given in Å, the angle between the Cp and the Cbd plane is given in°.…”
Section: Reactions Of 3a and 4a With Cpco(btsa)comentioning
confidence: 99%
“…In Table 2 the structural parameters of the cyclobutadiene ring of 11 are compared with those of 13 [17] and 14 (Scheme 5). [18] In the two "push-pull" systems 11 and 13 we find the shortest bond length between C3 and C4 and the longest bond length between C1 and C2.…”
Section: Reactions Of 3a and 4a With Cpco(btsa)comentioning
confidence: 99%